Subcutaneous veins depth measurement using diffuse reflectance images - Goh, C.M. (OSA - The Optical Society, 2017)
Intravenous (IV) procedures are often difficult due to the poor visualization of subcutaneous veins. Because existing vein locators lack the ability to assess depth, and also because mis-punctures and poor vascular access remain problematic, we propose an imaging system that employs diffuse reflectance images at three isosbestic wavelengths to measure both the depth and thickness of subcutaneous veins. This paper describes the proposed system as well as proof-of-principle experimental demonstrations. We initially introduce the working principle and structure of the system. All measurements were based on the Monte Carlo (MC) method and accomplished by referring an optical density (OD) ratio to a multi-layer diffuse reflectance model. Results were all validated by comparative ultrasound measurements. Experimental trials included 11 volunteers who were subjected to both ultrasound measurements and the proposed optical process to validate the system’s applicability. However, the unreliability of the “thickness” measurement of the vein may be due to the fact that the veins have collapsible walls – so excess pressure by the transducer will give a false thickness. © 2017 Optical Society of America